Recombinant Enzymatic Redox Systems for Preparation of Aroma Compounds by Biotransformation - Varga, Viktor; Štefuca, Vladimír; Mihálová, Lenka; Levarski, Zdenko; Struhárňanská, Eva; Blaško, Jaroslav; Kubinec, Robert; Farkaš, Pavel; Sitkey, Vladimír; Turňa, Ján; Rosenberg, Michal; Stuchlík, Stanislav (Frontiers in Microbiology, 2021)
The aim of this study was to develop immobilized enzyme systems that reduce carbonyl compounds to their corresponding alcohols. The demand for natural aromas and food additives has been constantly growing in recent years. However, it can no longer be met by extraction and isolation from natural materials. One way to increase the availability of natural aromas is to prepare them by the enzymatic transformation of suitable precursors. Recombinant enzymes are currently being used for this purpose. We investigated trans-2-hexenal bioreduction by recombinant Saccharomyces cerevisiae alcohol dehydrogenase (ScADH1) with simultaneous NADH regeneration by recombinant Candida boidinii formate dehydrogenase (FDH). In a laboratory bioreactor with two immobilized enzymes, 88% of the trans-2-hexenal was transformed to trans-2-hexenol. The initial substrate concentration was 3.7 mM. The aldehyde destabilized ScADH1 by eluting Zn2+ ions from the enzyme. A fed-batch operation was used and the trans-2-hexenal concentration was maintained at a low level to limit the negative effect of Zn2+ ion elution from the immobilized ScADH1. Another immobilized two-enzyme system was used to reduce acetophenone to (S)-1-phenylethanol. To this end, the recombinant alcohol dehydrogenase (RrADH) from Rhodococcus ruber was used. This biocatalytic system converted 61% of the acetophenone to (S)-1-phenylethanol. The initial substrate concentration was 8.3 mM. All enzymes were immobilized by poly-His tag to Ni2+, which formed strong but reversible bonds that enabled carrier reuse after the loss of enzyme activity.